Uji Senyawa Taurin Sebagai Antikanker Terhadap Jumlah Sel-Sel Leukosit Dan Sel-Sel Eritrosit Mencit (Mus musculus L.) yang Diinduksi Benzo (Î‘) Pyren Secara In Vivo - Maysa, Agra; Widiastuti, E. L.; Nurcahyani, N.; Busman, H. (Politeknik Negeri Lampung., 2016)
The aim of this research was to determine the effect of taurine supplementation on the totalcount of leucocyte cells and erythrocyte cells of mice that have been induced to benzo (?)pyrene in vivo. The parameters of this experiment were the total count of leucocyte cells anderythrocyte cells of mice (Mus musculus L.). This experiment was conducted in a completerandomized design by using six treatments, each in five replications. The mice were dividedinto six groups. Group I used as control were not given any treatment. Group II were given0,2 mL of oleum olevarum (olive oil) orally to the end of the experiment. Group III wereinduced to benzo (?) pyrene without being given any taurine. Group IV were given 7,8mg/bw of taurine before being induced to benzo (?) pyrene. Group V were given 7,8 mg/bwof taurine after being induced to benzo (?) pyrene. Group VI were given 15,6 mg/bw oftaurine after being induced to benzo (?) pyrene. Mice of group III, V, and VI were injectedwith 0,5 mL of benzo (?) pyrene solution every day for 10 days on their subcutant tissue forthe purpose of a nodule being formed in this area. It was then continued by giving taurineorally for 15 days. In the final treatment, mice blood was taken to count the leucocyte cellsand erythrocyte cells. The data were analyzed using ANOVA (Analysis of Variance) thencontinued by calculating least significant difference at 5 per cent level of significance. Theresults indicated that taurine had the ability to reduce leucocyte cells into its normalquantity, and was able to increase the number of erythrocyte cells of mice suffered fromleukaemia back to normal.Key words: benzo (?) pyrene, leukaemia, leucocyte, mice , taurine